Structure and composition of woody species in riparian forest in the university of agriculture, Abeokuta, Nigeria (2014)
Understanding the nattma of £/->s forests in She tropics is crucial So resource managers. Forests in Nigeria are if ;t at a high re'xs The structure and floristic composition of remaining forests are largely who m. Structure an / floristic composition in a riparian forest of the Federal University of Agriculture, Abeokuta, Niger*- f was assessed. Fifteen sample plots of 0.625ha each were used to assess all plants > 5cm diameter at breast height (dbh) in each plot for density, height dbh and frequency. Detrended Correspondence Analysis (DCA), similarity and diversity statistics were used to analyse the data am Importance Value Index estimated. The result of the study identified 504 individual woody speck s srom 25 species of 16 families. Papelionaceae had the highest species (4). Anmuriceae, Mimosacca ?, Myr&aceae, Cochlospermaceae, Euphorbiaceae, Apocynaceae and A vice.1 niaceae had 1 spe des each. DanieSHa oliveri had the highest density (302 plants/ha) and Impt ■Sauce Value It dex IVIJ of (108.01%). The lowest density was found in Bauhinia tcmentosa, Nan lea diderrichii. / d Maltheria indies (5 plants/hectare) and 1V1 of 2.85%, 5.10% and 2.39% res jecb'vely. The high si basal area was estimated for Danisilia oliveri (71.175m2), the lowest was re, arded far Maiadm ita- alnifolsm (0.107m2). The cumulative stem diameter class of 5-65cm s\ counted for 78. Id1} of the total number of stems in the forest estate. Tree height ranged from ■ 6.4 to 22.7m. Simps* 7s similarity and diversity index ranged between 0.143 to 0.875 and 0.43 to 0.89 respective y at J equitability index ranged from 0.61 to 0.93 for all the plots, while the basal ares ranged from 8.052m2/plot to 27.809nr/plot. High Eigen value (54%), the length of ordination space coverage (-2 to 4).Th@ location of pH the plots in the first quadrant indicates that the envimnmmt k stable; variation in the floristic composition between the plots Is minimal with high heterogeneity in the site and high species richness recorded reflects the heterogeneous distribution patt im in species compositioh. Conclusively, this study has shown that riparian forests may act as a catalyst for successful natural forest succession thus sustaining native forest flora and habitat for fastnp.